2003
DOI: 10.1177/021849230301100409
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane Grafts: A Viable Alternative for Dialysis Arteriovenous Access?

Abstract: Polyurethane grafts, promoted for their self-sealing properties and low complication rates, were recently introduced for hemodialysis access. We review our experience with this graft material to determine its complication and patency rates. Between January 1995 and December 1999, 118 patients, 75 female and 43 male, with a mean age of 51 years, had a total of 163 polyurethane arteriovenous grafts inserted. The grafts were mostly 6 mm in diameter (69.3%), placed in a loop configuration (91.4%) in the forearm (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 11 publications
2
26
1
2
Order By: Relevance
“…Nowadays, polytetrafluoroethylene (PTFE) and polyurethane (PVAG) are among the most frequently used vascular grafts in the world (1,6,11). Several studies have reported different complications and patency rates for these artificial grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, polytetrafluoroethylene (PTFE) and polyurethane (PVAG) are among the most frequently used vascular grafts in the world (1,6,11). Several studies have reported different complications and patency rates for these artificial grafts.…”
Section: Discussionmentioning
confidence: 99%
“…The prolonged survival of this group of patients depends on the long-term functioning and patency of the vascular access for hemodialysis (1). Prosthetic vascular grafts are inevitably used for patients whose vessels are unsuitable for an autogenous arteriovenous (AV) fistula due to several reasons, especially diabetes mellitus-derived atherosclerosis (2).…”
Section: Introductionmentioning
confidence: 99%
“…Since enrollment in the randomized study was limited to patients receiving an upper extremity graft (1), it is not clear whether its conclusions can be generalized to polyurethane grafts placed in the thigh. Other published series of polyurethane grafts have reported an infection rate of 3–30% (3–7). These studies varied in the proportion of patients receiving thigh grafts and in the time to first graft cannulation, and lacked appropriate control patients with PTFE grafts.…”
mentioning
confidence: 99%
“…Es ist das am meisten genutzte synthetische Material in der Dialyseshuntchirurgie. Daneben findet seit mehreren Jahren auch Polyurethan Verwendung [15,23].…”
Section: » Prothesenshunts Sind Für Permanente Dialyseshunts Nur Die unclassified